Antibodies of Double Stranded Deoxyribonucleic Acid and Antinuclear in Patients with Rheumatoid Arthritis: Comparison Study of Seropositive and Seronegative - Sura A.Abdulsattar1 , Abdullah Ali Mohammed2 , Mahmood Nazar Mustafa3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Rheumatoid arthritis is a heterogeneous disease, which can be, based on data combining genetic risk factorsand autoantibodies, sub-classified into positive and negative RA. The present study aims to establish acomparative analysis between seronegative and seropositive rheumatoid arthritis (RA), with regard toautoantibodies. A total of 151 patients with rheumatoid arthritis divided into two groups, Group A, 78patients with seropositive RA and Group B, 73 patients with seronegative RA. The measurements includedESR, CRP, RF, anti CCP,ANA, and anti dsDNA. Highly significant differences (p ? 0.01) in ESR (31.4 vs52.8 ml/hr), CRP (10.85 vs 23.59 IU/L), RF (8.34 vs 47.67 IU/L), anti CCP (21.72 vs 41.17IU/L), ANA(0.92 vs 2.3 IU/L), and anti dsDNA(13.01 vs 29.49 IU/L) levels. Significant correlation of anti dsDNA wereobserved with CRP, anti CCP (and ANA in seronegative RA. Meanwhile highly significant correlation wereobserved with ESR, CRP, and ANA in seropositive RA. Many of RA-associated autoantibody systems havebeen identified and recognize post translationally modified proteins, indicating the immunogenicity of suchproteins for human B cells. Among theme is anti dsDNA which may have a role of the inflammatory processof RA.